2006
DOI: 10.2166/wh.2006.013
|View full text |Cite
|
Sign up to set email alerts
|

Low risk for helminth infection in wastewater-fed rice cultivation in Vietnam

Abstract: This study was done to assess the risk of helminth infection in association with wastewater-fed rice cultivation in an agricultural setting of Nam Dinh city, Vietnam. In a cross sectional survey data were collected for 202 households in a commune where wastewater was used for irrigation and for 201 households in a commune that used river water. Parasitological examination was conducted on single stool samples obtained from 1,088 individuals aged ≥15 years from the households. The irrigation water used in both … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
38
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(43 citation statements)
references
References 13 publications
4
38
1
Order By: Relevance
“…For instance, Trang et al . found no increase in STH infections from exposure to wastewater in Vietnam. The interlinkages between different contamination sources and transmission routes are essential in these types of studies.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…For instance, Trang et al . found no increase in STH infections from exposure to wastewater in Vietnam. The interlinkages between different contamination sources and transmission routes are essential in these types of studies.…”
Section: Discussionmentioning
confidence: 87%
“…Independently of that, a review of the scarce literature shows an overwhelming evidence of increased risks of STH infections due to wastewater/sludge reuse [1,18,54,72,73] even if some studies were unable to establish links. For instance, Trang et al [74] found no increase in STH infections from exposure to wastewater in Vietnam. The interlinkages between different contamination sources and transmission routes are essential in these types of studies.…”
Section: Wastewatermentioning
confidence: 99%
“…Many farmers cannot afford treatment for some of the health problems caused by the exposure. Generally, farmers irrigating with wastewater have higher rates of helminth infections than farmers using freshwater, but there are exceptions (Trang et al, 2006). In addition, skin and nail problems may occur among farmers using wastewater (Van der Hoek et al, 2002;Trang et al, 2007).…”
Section: Implications For Farmers' and Consumers' Healthmentioning
confidence: 99%
“…However, in Vietnam, Trang et al . [17] found no evidence that rice cultivation with wastewater posed any significant helminth infection risk to farmers, even though they were exposed to wastewater containing 40–200 helminth eggs/L. Prevalence of and risk factors for helminth infections have been studied in Ghana [18].…”
Section: Introductionmentioning
confidence: 99%